Racism? Administrative and Community Perspectives in Data-Driven Decision Making: Systemic Perspectives Versus Technical-Rational Perspectives - Khalifa, Muhammad A.; Jennings, Michael E.; Briscoe, Felecia; Oleszweski, Ashley M.; Abdi, Nimo (Urban education (Beverly Hills, Calif.), 2014)
This case study describes tensions that became apparent between community members and school administrators after a proposal to close a historically African American public high school in a large urban Southwestern city. When members of the city’s longstanding African American community responded with outrage, the school district’s senior administration backed away from their proposal to close the school, despite making what it felt was a “neutral” and technical-rational decision. However, the local community interpreted this move as the historical continuation of racist behaviors and policies that had been experienced by the community over a period of several decades. Critical race theory (CRT) allows for an analysis regarding the nature of these beliefs about race and indicates the need for school administrators to engage the realities of the community members they serve, rather than merely enacting technical-rational administrative behaviors that serve to continue regimes of marginalization and oppression.